2007
DOI: 10.1074/jbc.m609297200
|View full text |Cite
|
Sign up to set email alerts
|

Gemin2 Plays an Important Role in Stabilizing the Survival of Motor Neuron Complex

Abstract: The survival of motor neuron (SMN) protein, responsible for the neurodegenerative disease spinal muscular atrophy (SMA), oligomerizes and forms a stable complex with seven other major components, the Gemin proteins. Besides the SMN protein, Gemin2 is a core protein that is essential for the formation of the SMN complex, although the mechanism by which it drives formation is unclear. We have found a novel interaction, a Gemin2 self-association, using the mammalian two-hybrid system and the in vitro pull-down as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 43 publications
6
60
0
Order By: Relevance
“…There is evidence that recruitment into SMN-gemin complexes stabilizes SMN, and in particular, gemin2 has been shown to play an important role in snRNP assembly through stabilization of the SMN oligomer/complex via novel self-interaction [34]. Other SMN-binding proteins have also been shown to regulate the stability of the SMN complex.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that recruitment into SMN-gemin complexes stabilizes SMN, and in particular, gemin2 has been shown to play an important role in snRNP assembly through stabilization of the SMN oligomer/complex via novel self-interaction [34]. Other SMN-binding proteins have also been shown to regulate the stability of the SMN complex.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have discovered that Gemin2 forms a homodimer responsible for the stability of the SMN oligomer/complex required for efficient snRNP assembly (22). Surprisingly, we also found that siRNA-mediated Gemin2 knockdown causes dissociation of several components including Gemin3 and Gemin7 from the SMN complex, suggesting that Gemin2 helps to stabilize other components in the SMN complex either directly or indirectly (22).…”
Section: Survival Motor Neuron (Smn)mentioning
confidence: 75%
“…Mammalian Two-hybrid Assay-Mammalian two-hybrid assays, including sample construction and transfection, were carried out as previously described (22). The linear doublestrand DNA constructs to express fusion proteins with the Gal4 DNA-binding domain (BIND) or the VP16 trans-activation domain (ACT) were prepared in a two-step PCR.…”
Section: Methodsmentioning
confidence: 99%
“…A small complex composed only of SMN and gemin 2 represents its inactive form whereas the high molecular form containing SMN, gemin 2, 3 and 4 is an active form that can bind substrates [17]. Gemin 2 plays a role in stabilization of the SMN complex [16], in export of smRNAs from the nucleus, and in their assembly in the cytoplasm [12].…”
Section: Introductionmentioning
confidence: 99%